Advocating for the right to food in South Africa - an analysis of judicial activism, public interest litigation and collective action in South Africa as a strategy to secure the right to food - Moyo, Busiso Helard (My University, 2016)
This dissertation is an investigation of the conditions that would bring about the legal enforcement of the right to access sufficient food in South Africa as premised on the Constitution. This is motivated by the fact that modern-society has seen a gradual increase in the occurrence of socio-economic rights being protected through the legal opportunity structure of countries, ultimately leading to public interest litigation. At present, the right to food is being violated in South Africa. Taking into account the ambit of the constitution and several international instruments that speak to its realisation and the fact that there has been litigation on other socio-economic rights, suggesting that tools for litigation are in place, it is perplexing that right to food litigation has not taken place. The research question of this paper is therefore: which factors and conditions would have to be present for there to arise public interest litigation on the right to food in South Africa? Due to the fact that literature on right to food litigation is almost non-existent, especially for the African context, this is an explorative case study. The dissertation utilises an analytical framework to study the prospect of litigation on the right to food becoming a reality. The study is largely theory-driven, relying on various sources of evidence: secondary literature, conducted-research and official state documents speaking to the countries right to food narrative. The analysis reveals that there are many barriers to right to food litigation in South Africa. These mainly have to do with the conditions that impact the manner in which right to food violations are understood by the poor and marginalised in society on one hand and the responsiveness of the courts to the voice of the marginalised and poor on the other. The dissertation concludes that the most crucial factors for right to food litigation in South Africa to arise are the need for more information and awareness around the right to food; improved legal assistance for the hungry and poor; more trust in the legal system amongst those at the bottom of the pyramid; the need for a stronger focus on litigation strategies by civil society and advocacy groups and the need for judges to be more innovative in carrying-out their duties. The conclusions of this study have relevance for those working actively for the promotion and realisation of the right to food in South Africa.
A dissertation submitted in fulfilment of the requirements for the degree of Masters of Arts by Dissertation to the School of Social Sciences, University of the Witwatersrand, Johannesburg, 2016
Keywords: Food relief; Hunger; Poverty; Human rights--South Africa; Public interest law--South Africa